KAJIAN PELAKSANAAN PENGEMBAGAN DESA TANGGUH BENCANA DI GAMPONG PAYATIENG KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR - Ariyani .; Dirhamsyah .; Nizamuddin . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
The establishment and development of disaster resilient village (Destana) is one of the priority programs of the National Disaster Management Board (BNPB) which was conducted in Payatieng Village, Aceh Besar. It is expected that after the implementation of the program, which had resulted a number of disaster management documents at village level, the village community can build the cultures of mitigation, preparedness and community empowerment to become a more resilient and independent community in coping with any disaster threats. This research studied the level of community knowledge and manner in Payatieng Village post the Destana program, their participation level, the synchronization of the program with the village development program and the extent of the impact of the program on community life. This research used quantitative and qualitative method. The source of the data consists of primary data (field research) and secondary data (library research). The analysis result showed that the community participation level in the implementation of the Destana Program, for those who are directly involved in it, are 80% good and 20% very good. While for those who are not directly involved in the program showed 80% good and 20% fair. This indicates that the community participation level in the development of resilient village in Payatieng Village is in good category. The synchronization of the Destana program with the village development program also has been very good. It can be seen from the integration of disaster risk reduction measures into the sustainable village development program that stated in the medium-term development program (RPJM) of Payatieng Village year 2016-2022. The Destana program has highly impacted the community life in Payatieng Village, especially on the development of the creative economy, by sticking to the disaster risk reduction measures that stated in the RPJM document.Keywords: Knowledge and manner, Participation, Synchronization, Disaster resilient village